Structure-based prediction of the stability of transmembrane helix–helix interactions: The sequence dependence of glycophorin A dimerization - MacKenzie, Kevin R. (The National Academy of Sciences, 1998)
The ability to predict the effects of point mutations on the interaction of α-helices within membranes would represent a significant step toward understanding the folding and stability of membrane proteins. We use structure-based empirical parameters representing steric clashes, favorable van der Waals interactions, and restrictions of side-chain rotamer freedom to explain the relative dimerization propensities of 105 hydrophobic single-point mutants of the glycophorin A (GpA) transmembrane domain. Although the structure at the dimer interface is critical to our model, changes in side-chain hydrophobicity are uncorrelated with dimer stability, indicating that the hydrophobic effect does not influence transmembrane helix–helix association. Our model provides insights into the compensatory effects of multiple mutations and shows that helix–helix interactions dominate the formation of specific structures.